Exploring the Use of Code-Switching and Code-Mixing Among EFL Faculty Members in Digital Learning Environments - Mala Rohmana, Wahyu Indah; Salsabil, Anisa Jihan (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
This study aims to investigate the use of code-mixing and code-switching by English as a Foreign Language (EFL) faculty members in the digital learning environment. While code-switching and code-mixing have been examined in various educational contexts, there remains a notable gap in understanding their intentional use within the digital learning environment, where faculty members deliberately alternate or mix languages to enhance clarity, engage students, and achieve specific teaching objectives in an online context. This study addresses this gap by examining how faculty members strategically employ these linguistic phenomena to enhance the learning experience in technologically mediated instructional settings. Employing qualitative research design and a case study approach, data were collected through documentation, observation, and semi-structured interviews. Two experienced EFL faculty members from a university in Malang, Indonesia, were selected as participants due to their expertise in code-switching and digital learning environments. The findings reveal complex code-mixing patterns, including inner, outer, and hybrid forms, while code-switching is observed in interlanguage transitions and shifts between formal and informal language. EFL faculty members intentionally utilize these linguistic strategies to enhance student comprehension. Switching between languages helps explain difficult concepts, clarify ideas, and foster better understanding. Bilingualism and situational context emerge as key factors influencing language choices in the digital learning environment, shaping the pedagogical practices for EFL educators. The implications of this study highlight the strategic role of language alternation in technologically mediated instructional settings, emphasizing its potential to enrich the pedagogical approaches of EFL educators in digital learning environments.